2007
DOI: 10.1007/s11187-007-9077-7
|View full text |Cite
|
Sign up to set email alerts
|

The impact of public guarantees on credit to SMEs

Abstract: Causal effect, Credit rationing, Difference-in-difference, SME, State-fund guarantee, G14, G21, G28, L26,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
74
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(80 citation statements)
references
References 16 publications
3
74
0
2
Order By: Relevance
“…4 We should note that the impact of public intervention upon financial constraints, that are not specific to the innovation process, has been previously analysed, even though with different methodologies (e.g. Zecchini and Ventura, 2009). appropriability and knowledge spillovers (Hall and Lerner, 2010). In this line, the main empirical issue is whether subsidies stimulate or replace R&D spending (David et al, 2000).…”
mentioning
confidence: 99%
“…4 We should note that the impact of public intervention upon financial constraints, that are not specific to the innovation process, has been previously analysed, even though with different methodologies (e.g. Zecchini and Ventura, 2009). appropriability and knowledge spillovers (Hall and Lerner, 2010). In this line, the main empirical issue is whether subsidies stimulate or replace R&D spending (David et al, 2000).…”
mentioning
confidence: 99%
“…They applied a difference in difference analysis and showed that the median value of bank debt was higher by 12.4% for guaranteed firms relative to the others. While admitting such value was on the low side compared to other studies, Zecchini and Ventura (2009) suggest that this evidence correlates with the high degree of selectivity in targeting SME groups in Italy and, when compared to other examples, the Italian SGS scheme had historically managed to limit default rates and contain the public subsidy. In addition, the guarantee enabled participating firms to reduced borrowing costs between 16% and 20% at the median point compared to nonguaranteed firms.…”
Section: Does the Intervention Bring About Improved Access In Credit mentioning
confidence: 71%
“…There is a general perception that SMEs are seriously disadvantaged in financial markets. With fewer assets and lacking a track record, small firms experience tighter financial constraints from the banking sector compared to other firms (Zecchini and Ventura 2009). In a debate spanning almost 4 decades, various authors (Green 2003;Roper 2011) suggest that this is due several factors including high administrative costs of small-scale lending, asymmetric information, inadequate collateral and the overall riskiness of these early stage businesses.…”
Section: Other System Level Concernsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, there is limited evidence of the effectiveness of these programs or policies through experimental and quasi-experimental evaluations. The current literature has mainly focused on certain types of interventions, such as microfinance (Aroca, 2002;; Banegas et al, 2002;; Dunn and Arbunckle, 2001;; McNelly et al, 1996;; Mosley, 2001) and loan guarantee programs (Arráiz, Meléndez, and Stucchi, 2014;; Chandler, 2012;; Kang, Heshmati, and Choi, 2008;; Zecchini and Ventura, 2009 Paravisini (2005). These studies generally show a positive effect of access to credit on investment and production growth, as well as an improvement in loan conditions.…”
Section: Introductionmentioning
confidence: 99%